Strategi Guru Dalam Mengidentifikasi Dan Mengembangkan Kecerdasan Majemuk Anak Usia Dini - Fauziah Nasution; Eka Damayanti Hasibuan; Diana Siregar; Khofifa Juliana; Sulaika Marito Nst (CV Edujavare Publishing, 2025)
This study aims to reveal teachers’ strategies in identifying and developing multiple intelligences of early childhood students at TK Nurul Muslimin. The main method used is qualitative research with a case study approach. Data were obtained through observation, interviews, documentation, and field notes during the learning process. The results show that intelligence identification was conducted through naturalistic observation, scheduled recording, and collaborative reflection, while development was implemented through thematic learning integrated with multisensory stimuli for various intelligences. This strategy proved effective in enhancing dominant intelligences and stimulating other potentials. These findings emphasize the importance of holistic and adaptive approaches to early childhood education based on multiple intelligences.